The Influence of Workload and Training on Employee Performance Through Job Satisfaction as an Intervening Variable (A Study at Mazarzo Traditional Wedding Organizer) - Sabiila, Hadaana; Prabowo, Budi; Nugroho, Rusdi Hidayat; Kusumasari, Indah Respati (Dinasti Publisher, 2025)
Abstract: This research aims to analyze the influence of workload and training on employee performance with job satisfaction as an intervening variable at Mazarzo Traditional Wedding Organizer. The background of this research is based on the high demand for services that is not proportional to the available human resources, as well as the suboptimal employee training that may reduce performance. The approach used is quantitative, employing methods such as observation, interviews, and questionnaires, with a saturated sampling technique involving 53 employees as respondents. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the SmartPLS 4.0 software. The results of the study indicate that: (1) workload has a positive and significant effect on job satisfaction; (2) workload has a negative and insignificant effect on employee performance; (3) training has a positive and insignificant effect on job satisfaction; (4) training has a positive and insignificant effect on employee performance; (5) job satisfaction has a positive and significant effect on employee performance; (6) workload has a positive and significant effect on employee performance through job satisfaction; (7) training has a positive and insignificant effect on employee performance through job satisfaction. These findings highlight the importance of proportional workload management and structured training to optimally enhance employee satisfaction and performance..